The report of women victims of domestic violence: a literature review (Research, Society and Development, 2020)
This study aimed to analyze qualitative scientific articles that contained reports of women victims of domestic violence. The search was carried out on the CAPES and SciELO journals portal, and 15 studies were selected that met the following inclusion criteria: scientific articles available in full for free; published in the last five years (2015-2019); written in Portuguese; national; peer-reviewed; with a qualitative approach. During the characterization of the studies, it was found that most articles had frequency of publications in the years 2015 and 2019, as well as in journals with a Qualis A2 stratum. The literature review technique was adopted, with a quantitative and qualitative approach and content analysis. After the process of categorizing the studies, 8 thematic categories emerged in which the most frequent was: types of violence (f = 12), with categorical incidence in 12 articles and the least frequent was education (f = 2), with an incidence categorial in 2 articles. Furthermore, the word cloud technique was used, in which the 10 most frequent terms are perceived in the objectives of the articles, the textual corpus of this analysis, the most frequent being: women (f = 15) and violence (f = 15), and the least frequent: attended (f = 3), attendance (f = 3), understanding (f = 3) and history (f = 3). It is emphasized the need to develop new research on the theme to understand the phenomenon of violence against women and the improvement of public policies to face domestic violence.